Grocery retail market concentration convergence in Eastern European and Baltic EU member states in 2010-2019 - Danusevics, Martins (University of Latvia, 2021)
The paper analyses market concentration development in the Chech Republic, Estonia, Hungary, Latvia, Lithuania, Poland, Slovakia and Slovenia. It is determined that these countries have a converging market concentration tendency indicating a decrease in the competition level and becoming more homogeneous. At the same time there are strong indications for market concentration being linked also to retail turnover.
Keywords: retail; competition; market concentration; Research Subject Categories::SOCIAL SCIENCES::Business and economics